Treatment patterns and burden of complications associated with sickle cell disease: A US retrospective claims analysis. Issue 4 (6th October 2022) - Manwani, Deepa; Burnett, Arthur L.; Paulose, Jincy; Yen, Glorian P.; Burton, Tanya; Anderson, Amy; Wang, Sara; Lee, Soyon; Saraf, Santosh L.
Abstract: Complications associated with sickle cell disease (SCD) that are highly impactful for patients but until recently have been less understood include priapism, nephropathy, and neurologic injury. We conducted a retrospective study using US administrative claims data from July 01, 2013 through March 31, 2020 to analyze incidence of these complications, SCD treatment patterns, and healthcare resource utilization (HCRU) and costs among 2524 pediatric and adult patients with SCD (mean [SD] age 43.4 [22.4] years). The most common treatments during follow‐up were short‐acting opioids (54.0% of patients), red blood cell transfusion (15.9%), and hydroxyurea (11.0%). SCD complications occurred frequently; in the overall population, the highest follow‐up incidences per 1000 person‐years were for acute kidney injury (53.1), chronic kidney disease (40.6), and stroke (39.0). Complications occurred across all age groups but increased in frequency with age; notably, acute kidney injury was 69.7 times more frequent among ages 65+ than ages 0–15 ( p  < 0.001). Follow‐up per‐patient‐per‐month HCRU also increased with age; however, all‐cause healthcare costs were similarly high for all age groups and were driven primarily by inpatient stays. Patients with SCD across the age spectrum have a high burden of complications with the use of current treatments, suggesting unmet needs for treatment management.